Characterization of international migration movements toward Chile: A scoping review of scientific articles and official reports - Reinoso-Cataldo, María Belén; Stuardo, Valeria; Bustos-Ibarra, Cecilia; Belmar, Julieta; Lisboa, Cristian; Low, Kenny; Rubio, Sonia Parella; Parra, Constanza Adrian; Carrasco-Portiño, Mercedes (Journal of migration and health (Online), 2025)
In the last decade, Chile has emerged as a receiving country for migrants from Latin America and the Caribbean (LAC). The scale of this phenomenon has sparked increasing interest in understanding its impact on various sectors such as healthcare and education. This study aims to characterize the scientific evidence and official reports on international migration toward Chile from 1990 to 2024. A scoping review was conducted. Global inclusion criteria: These encompassed articles and official reports published between 1990 and 2024 focusing on the migrant population toward Chile. Databases for the articles: These included PubMed, Scopus, WoS, and SciELO. Keywords: These included Transients and Migrants, Emigration and Immigration, Population Dynamics, Human Migration, Chile, South America, Latin America, and Freedom of Movement. Sources for the official reports: These included National Statistics Institute (INE for its acronym in Spanish); Department of Immigration and Foreign Services; Jesuit Migrant Service; National Human Rights Institute (INDH for its acronym in Spanish); and The UN Refugee Agency (UNHCR). No keywords were used. Global variables: These included type of study, sociodemographic characteristics, type of migration, object of study, main results, limitations, and conclusions. A concordance test of the questionnaire was conducted for the articles and official reports, yielding 91 % and 94 % agreement between observers, respectively. Accordingly, 21 articles and 28 official reports were included. In both types of sources, the study population included the entire life cycle, primarily from countries in LAC. The observed types of migration included international (voluntary, forced, or humanitarian). Articles focused on measuring mental health (MH) and the access/use of healthcare services. Regarding MH, it was observed that the young migrant population exhibited worse indicators than the adult population, while both migrant and Chilean populations exhibited similar MH statistics, with socioeconomic level (SEL) being a significant determinant. Access to healthcare services has increased among the migrant population and is contingent upon SEL. Only two articles have addressed subjects related to reproductive health, with none discussing sexual health. Official reports focused on characterizing the population and their access to services (healthcare, education, housing, occupational situation), border mobility, poverty index, social perceptions, and inclusion. Most studies have utilized secondary data provided by official sources. Migration toward Chile primarily involves south–south migration, sociodemographic characterization, and issues accessing services, including healthcare. Results highlight a scarcity of studies collecting primary data, leading to a lack of relevant indicators for understanding aspects such as migration causes, attracting factors, migration trajectory, migration status, cross-cultural relationships, or sexual health.